Positive taxis and sustained responsiveness to water motions in larval zebrafish - Groneberg, Antonia H.; Herget, Ulrich; Ryu, Soojin; De Marco, Rodrigo J. (Frontiers in Neural Circuits, 2015)
Larval zebrafish (Danio rerio) have become favored subjects for studying the neural bases of behavior. Here, we report a highly stereotyped response of zebrafish larvae to hydrodynamic stimuli. It involves positive taxis, motion damping and sustained responsiveness to flows derived from local, non-stressful water motions. The response depends on the lateral line and has a high sensitivity to stimulus frequency and strength, sensory background and rearing conditions - also encompassing increased threshold levels of response to parallel input. The results show that zebrafish larvae can use near-field detection to locate sources of minute water motions, and offer a unique handle for analyses of hydrodynamic sensing, sensory responsiveness and arousal with accurate control of stimulus properties.